2020
DOI: 10.1021/acs.iecr.9b04943
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Regression and Soft Computing Models to Maximize the Methane Storage Capacity of Anthracite-Based Adsorbents

Abstract: Adsorbed natural gas (ANG) technology is a safe and low-cost approach for natural gas storage. Improving the volumetric adsorption capacity of adsorbents in the ANG tank can enhance the fuel density and make this technology cost-effective compared to other available CH4 storage approaches. For this purpose, the present research focuses on maximizing CH4 uptake on low-cost and available anthracite-based carbon materials via experimental and analytical investigations. The effect of preparation variables of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…† Positive marks in front of each term represent the synergistic effect and consequence to elevate in the corresponded responses, while negative signs indicate antagonistic effects and decrease the response. 33,45 The ANOVA results for tting the suggested model for entire responses are exhibited in Tables 4 and 5.…”
Section: Empirical Methods For Collected Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…† Positive marks in front of each term represent the synergistic effect and consequence to elevate in the corresponded responses, while negative signs indicate antagonistic effects and decrease the response. 33,45 The ANOVA results for tting the suggested model for entire responses are exhibited in Tables 4 and 5.…”
Section: Empirical Methods For Collected Experimental Datamentioning
confidence: 99%
“…Statistical assessment accomplished by Mirzaei et al revealed that tuning the parameters of the RSM and ANN enables us to effectively predict methane adsorption capacity on the carbon active samples. 33 In the present study, collections of the Pt-Cr/Zr(x)-HMS catalysts with various Cr/Zr molar ratios were synthesized and utilized as solid acid catalysts for the catalytic isomerization of n-heptanes. In order to examine the catalyst performances, parameters such as activity and various forms of the selectivity including MOB (mono-branched) heptane, MUB (multibranched) heptane, i-C 7 (MOB + MUB), cracking (crack.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that mathematical models are powerful tools for simulation and optimization of chemical reaction systems 25,26 . Among them, the statistical models would facilitate correlating operating parameters and provide a better view of the performance of the experimental processes.…”
Section: Methodsmentioning
confidence: 99%
“…The activated carbons (ACs) were prepared by chemical activation of anthracite as the raw material. The chemical activation process was carried out according to the optimised activation conditions reported in our previous study [22] to maximise the CH4 storage capacity of the prepared adsorbents. The specific optimisation condition including chemical impregnation ratio, activation temperature and retention time were obtained via two different well-known methods of surface response methodology and genetic algorithm to be 3 g KOH/g anthracite, 730 • C and 60 min, respectively.…”
Section: Preparation Of the Carbon Adsorbentsmentioning
confidence: 99%
“…A custom-built volumetric adsorption measurement apparatus was used for the analysis of CH4 and H2 uptake on the prepared adsorbents at 298 K and pressure up to 40 bar. We have described the details of this sorption measurement system, calibration method and measurement procedure in our previous studies [22,25] and briefly in the Supplementary Information.…”
Section: Characterisation Of the Activated Carbonsmentioning
confidence: 99%